Pourous nanoparticles formation using a dendrimer template. Issue 3 (2010) - Bonaccorsi Bonaccorsi, L. L.; Lombardo Lombardo, D. D.; Longo Longo, A. A.; Proverbio Proverbio, E. E.; Calandra Calandra, P. P.
Abstract : We describe the synthesis of porous spherical nanoaggregates derived by the controlled growth of zeolite LTA on a poliamidoamine (Pamam) dendrimer acting as nano-template. The presence of a strong condensed cationic Na + charge all around the dendrimers, which is responsible for the intense electrostatic inter-particle interaction potential, stimulate the condensed growth of the zeolitic phase onto the dendrimer substrate. Moreover, the screening produced by the zeolite grown on the dendrimer surface promote the entanglement process between the primary units with the formation of large porous clusters. The main features of the self-assembly process has been characterised by means of different techniques such as Small Angle X-ray Scattering (SAXS), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD) and Energy Dispersive X-ray (EDX) microprobe spectroscopy. The finding of our results may open new perspectives in the synthesis of organic–inorganic nanostructured materials based on mesoporous frameworks with new characteristics and properties.